LHC Physics. - Binoth, T. (Scottish graduate series., 2012)
Exploring the phenomenology of the Large Hadron Collider (LHC) at CERN, LHC Physics focuses on the first years of data collected at the LHC as well as the experimental and theoretical tools involved. It discusses a broad spectrum of experimental and theoretical activity in particle physics, from the searches for the Higgs boson and physics beyond the Standard Model to studies of quantum chromodynamics, the B-physics sector, and the properties of dense hadronic matter in heavy-ion collisions. Covering the topics in a pedagogical manner, the book introduces the theoretical and phenomenological f.